Study New Pyridine Derivatives as Corrosion Inhibitors for Mild Steel in an Acidic Media - Kareem, Rania; Salih Shihab, Mehdi (Al-Nahrain Journal of Science, 2021)
Some new pyridinium salts, namely 4-(4-bromo-benzylidene-hydrazinocarbonyl)-1-phenyl-pyridinium bromide, A1; 4-(4-bromo-benzylidene-hydrazinocarbonyl)-1-butyl-pyridinium bromide, A2; 4-(4-bromo-benzylidene-hydrazinocarbonyl)-1-phencyl-pyridinium bromide, A3; were synthesized and studied as corrosion inhibitors for mild steel in 1M H2SO4 aqueous solution at 20°C by weight loss measuring for 24 hrs. The results showed that the inhibition efficiency of all pyridinium bromide derivatives had a significant in value with the highest concentration. An increase in the inhibitor concentration is accompanied by a decrease in the corrosion rate, an increase in the retarding efficiency and an increase in the degree of surface coverage. The values of the free energy of adsorption revealed the effects of spontaneously reaction of (A1, A2, and A3) and gave useful information to predict the interaction between the metal surface and the organic molecules as corrosion inhibitors.